Analysis of choroidal macular thickness in early post-Covid-19 patients - Jesus, Jeniffer Domingues de (2021)
Corona Virus Disease 2019 (COVID-19) is considered a critical global health challenge. Several investigations have suggested vascular dysfunction caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection, but regarding ophthalmic involvement, only few data are available. Our aim was to evaluate the choroidal involvement in post-COVID-19 patients. 40 eyes from 40 patients with previous SARS-CoV-2 infection and 40 eyes from 40 age matched controls were included. Choroidal measurements were made using Enhanced Depth Imaging Optical Coherence Tomography (EDI-OCT) at 13 different locations: at central fovea and at intervals of 500μm to 1500μm away from the fovea in the temporal, nasal, superior and inferior regions. Post-COVID-19 patients showed a significant increase in choroidal thickness compared with the control group for all the regions analyzed (all p <0.01). In the Post-COVID-19 group, the choroid is thickest subfoveally and thinnest 1500μm nasal from fovea. In both groups, the superior and temporal macular choroid has been measured thicker than the inferior and nasal macular choroid, respectively. Our results cautiously suggest that post-COVID-19 patients showed an increase in choroidal thickness compared to control groups. This choroidal thickening may reflect the importance of vascular factors in the pathogenesis of SARS-CoV-2 infection. Keywords: Choroid; COVID-19; Hemodynamic Changes; Ocular Circulation; Retina; SARS-CoV-2